Room Temperature Phosphorescence of Chlorine Doped Carbon Nitride Dots - Patir, Khemnath; Gogoi, Sonit Kumar (Frontiers in Chemistry, 2022)
Metal free room temperature phosphorescent materials have been the subject of considerable attention due to their potential applications in optoelectronic devices sensing, and security and safety signage. This study discusses how efficient fluorescent and phosphorescent chlorine doped carbon nitride dots (Cl-CNDs) were prepared by thermal treatment of guanidine hydrochloride. The Cl-CNDs prepared were characterized by field emission scanning electron microscope, dynamic light scattering, PXRD, EDX, Thermo gravimetric analysis, FT-IR, and UV-Visible spectroscopy. The Cl-CNDs exhibit a long phosphorescence lifetime of 657 ms and the phosphorescence quantum yield was found to be 2.32% upon being excited at 360 nm in ambient conditions. Formation of compact coreparticles via condensation along with hydrogen bonding of Cl-CNDs by its functional groups facilitate intersystem crossing and stabilizes the triplet states, favoring room temperature phosphorescence. The cost effective preparation and tunable optical properties of Cl-CNDs may find applications in security encryption and optoelectronic devices.